Extent of Challenges Encountered By the Araling Panlipunan and Social Science Teachers in Facilitating the Modular Distance Learning: Basis for the Formulation of Learning and Development Plan - Pamogas, Marino (JPAIR Institutional Research, 2022)
Modular Distance Learning is one of the learning modalities in the new normal using teacher-made modules with learning tasks based on the Most Essential Learning Competencies (MELCs). This online descriptive quantitative research investigated the extent of challenges faced by the Araling Panlipunan and Social Science teachers from the ten districts of the Schools Division Office of Surigao City for the school year 2020-2021, in which purposive sampling was used. Mean and standard deviation were the statistical tools used to treat the data. In a nutshell, the result reveals a moderate difficulty encountered by the teacher-respondents in facilitating modular distance learning, with an overall mean of 2.78 and a standard deviation of 0.71. These struggles manifest because handling modular classes during the pandemic was a surprise. The specific findings show that the Development of Self-Learning Modules (SLMs) and Quality Assurance topped the challenges of teachers. Other factors, such as Production, Distribution, Retrieval of SLMs, and Learning Assessment and Monitoring, exhibit a low to moderate degree of difficulty. Despite this COVID-19 pandemic, teachers have continually facilitated the educative processes. However, they should be more capacitated to equip themselves with relevant knowledge and skills on the rudiments of preparing the aforementioned learning resources as supplemental learning materials, in-person learning engagement, and even other applicable learning platforms.